La constitucionalización del derecho administrativo - Landa, César (2016)
The link between Administrative Law and Constitutional Law, branches of Public Law, is undeniable. It is even more patent currently with the phenomenon of the constitutionalization of Law.In this article, the author analyses this phenomenon in the field of Administrative Law, the administrative-constitutional principles, and examines how various institutions of Administrative Law have been constitutionally configurated,outlined and controlled in Peru, for which he goes over the most important jurisprudence of the Peruvian Constitutional Court regarding the matter.